The effect of different sterilization methods on the shelf life and physicochemical indicators of fermented pork jerky - Zhao, Changqing; Dai, Jinping; Chen, Feifei; Zhao, Zhifeng; Zhao, Xingxiu (Frontiers in Nutrition, 2023)
To determine the effect of different sterilization methods on shelf life and physicochemical parameters of fermented pork jerky. Various sterilization techniques, including boiling, pasteurization, medium-temperature steam sterilization, high-temperature steam sterilization, ultrasonic sterilization, and ultraviolet sterilization, were employed in this study to treat vacuum-sealed fermented pork jerky.Changes in microbial populations, physicochemical parameters, and sensory evaluations were monitored throughout the storage period. The results indicated the presence of Staphylococcus aureus on the 24th, 21st, 33rd, 24th, 18th, and 15th days in pork jerky subjected to boiling (100°C, 20 min), pasteurization (85°C, 15 min), medium-temperature steam sterilization (105°C, 0.5 Pa, 30 min), hightemperature steam sterilization (121°C, 1.0 Pa, 20 min), ultrasonic sterilization (480 W, 30 kHz, 30 min), and ultraviolet sterilization (254 nm, 100 W/m², 60 min), respectively. Coliforms, salmonella, and Shigella were not detected in any group during storage. The medium-temperature steam sterilization method yielded the most favorable microbiological results, with an aerobic plate count of less than 1.0 lg CFU/g. However, other physicochemical parameters and sensory evaluations were moderate, with total volatile basic nitrogen (TVB-N) and thiobarbituric acid reactive substances (TBARS) measuring 14.023 mg N/100 g and 0.427 mg MDA/kg, respectively, remaining within acceptable limits. Therefore, considering microbiological indicators as the primary determinant of shelf life and taking into account other physicochemical parameters, the medium-temperature steam sterilization method was identified as the most suitable approach for extending the shelf life of fermented pork jerky while preserving its flavor.